An integrated measurement method for complex micro-scale geometries - Rabani, Amir; Senin, Nicola; Helmli, Franz; Butler-Smith, Paul; Leach, Richard K. (2016)
Micro-scale geometries are becoming commonplace in many high-precision manufacturing applications. Micro-drilling processes, for example, are being employed for producing holes in demanding applications involving fluid transfer, atomisers and micro-mechanics. This paper explores the measurement and characterisation of a high aspect-ratio micro-hole (nominal diameter approximately 1000 pm, aspect-ratio 1:10), produced using abrasive waterjet in Ti6AI4V. X-ray computed tomography, contact micro-coordinate metrology and focus-variation microscopy are used for measuring the hole surfaces, and dedicated computational geometry algorithms are applied to obtain critical hole dimensions, such as radius as a function of depth. The comparison of the measurement and characterisation results obtained by means of the different solutions explored hints at new approaches for multisensor data fusion that can help reduce bias in the measurement of high aspect-ratio micro-scale features.